2013
DOI: 10.3945/jn.112.167064
|View full text |Cite
|
Sign up to set email alerts
|

Low-Methoxyl Pectin Stimulates Small Intestinal Mucin Secretion Irrespective of Goblet Cell Proliferation and Is Characterized by Jejunum Muc2 Upregulation in Rats

Abstract: Generally, soluble fibers increase small intestinal mucin secretion by increasing the number of goblet cells in a viscosity-dependent manner. The present study aimed to examine the mechanism by which low-methoxyl pectin (LPC) affects mucin secretion in the small intestine. First, diets containing 50 g/kg of low-viscosity fiber (LPC, gum arabic, guar gum, low-molecular konjac mannan, arabinogalactan, sodium alginate) or high-molecular konjac mannan (KMH) were fed to Wistar rats for 10 d. Luminal mucin was great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…It should be taken also into consideration that Thr‐imbalanced diet may interact directly with epithelium and enhance or impair mucin release from GC without changes in GC number. However, that mechanism of stimulation of mucin secretion was observed only in the jejunum of rats fed diet containing low‐methoxyl pectin (Hino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken also into consideration that Thr‐imbalanced diet may interact directly with epithelium and enhance or impair mucin release from GC without changes in GC number. However, that mechanism of stimulation of mucin secretion was observed only in the jejunum of rats fed diet containing low‐methoxyl pectin (Hino et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LMP easily penetrates the mucin layer of the intestine wall [21], which facilitates the interaction of LMP with the intestinal epithelia. It is found that LMP but not HMP stimulate small intestinal mucin secretion by direct interaction with the epithelium [22].…”
Section: Introductionmentioning
confidence: 95%
“…Low-methoxylation pectin is typically used for drug delivery, gene delivery, wound healing, tissue reparation, and in edible films (Espitia, Du, Avena-Bustillos, Soares, & McHugh, 2014;Munarin, Tanzi, & Petrini, 2012). Notably, low-methoxylation pectin is fermented more rapidly than highmethoxylation pectin (Dongowski, Lorenz, & Proll, 2002) and protects epithelial cells by stimulating intestinal mucin secretion (Hino et al, 2013).…”
Section: Properties Of Dfs From Fruits and Vegetablesmentioning
confidence: 99%